Digital Transformation in Motor Vehicle Tax Administration: Evaluation of the e-Samsat System and its Impact on Taxpayer Compliance in Indonesia - Andi Arif; Susanti, Gita; Rusdi, Muhammad (KnE Social Sciences, 2025)
Digitalization in public administration in Indonesia is rapidly advancing, one of which is the implementation of digital systems in motor vehicle tax (PKB) payment. Applications such as e-Samsat, SAKPOLE, and SIGNAL are part of the digital transformation aimed at improving tax administration efficiency and taxpayer compliance. This study examines the implementation of these applications in simplifying the motor vehicle tax payment process, as well as their impact on taxpayer compliance and the effectiveness of digital governance policies. Using a qualitative approach and literature analysis, the study finds that while digital systems like e-Samsat provide easier access for taxpayers, challenges such as limited digital literacy and uneven infrastructure still hinder optimal implementation. The study results indicate that the digitalization of motor vehicle tax services can increase efficiency, transparency, and public participation in tax payments, ultimately strengthening tax compliance. However, to achieve optimal results, there is a need for improved digital infrastructure, more intensive socialization, and training for those unfamiliar with technology. This research offers recommendations to expand the reach of tax digitalization by considering technological readiness in each region and emphasizing digital education for the public.